Childfree employees: The effects of flexible work arrangements and childfree-friendly culture on organisational commitment - Jacobs, Albertus Abraham (Organisational Psychology, 2017)
Organisations are increasingly introducing flexible workplace practices and policies such as flextime and flexplace to increase the commitment of their employees and assist them to balance the competing work-life demands. At first, they were designed to create a family-friendly workplace for working mothers and, later, also for working fathers. Childfree employees (i.e., those with no children) were not included. There is little research on the impact of these work arrangements on the organisational commitment of these childfree employees. This dissertation tries to close that gap. Childfree employees (N = 134) working in over a dozen South African organisations participated in a self-report quantitative survey. It seems that the availability and use of flexible work arrangements did not significantly predict their organisational commitment. Organisational commitment related to only one dimension of the childfree-friendly culture scale, equal work expectations. Perceived organisational support (POS) mediated the relationship between organisational commitment and equal work expectations.